Understanding the Link Between Burnout and Sub-Optimal Care: Why Should Healthcare Education Be Interested in Employee Silence? - Montgomery, Anthony; Lainidi, Olga (Frontiers in Psychiatry, 2022)
Evidence on the association of burnout with objective indicators of performance is scarce in healthcare. In parallel, healthcare professionals ameliorate the short-term impact of burnout by prioritising some tasks over others. The phenomenon of employee silence can help us understand the evolution of how culture is moulded towards the prioritisation of some tasks over others, and how this contributes to burnout. Silence in healthcare has been associated with concealing errors, reduced patient safety, and covering up errors made by others. Conversely, there is evidence that in organizations where employees are encouraged to speak up about concerns, and where concerns are responded to appropriately, better patient outcomes such as improved patient safety and patient experience occur. Interventions to promote ‘speaking-up’ in healthcare have not been successful and are rooted in a professional culture that does not promote speaking out. In this paper, we review the evidence that exists within healthcare to argue why healthcare education should be interested in employee silence, and how silence is a key factor in understanding how burnout develops and impacts quality of care. The following key questions have been addressed; how employee silence evolves during medical education, how is silence maintained after graduation, and how can leadership style contribute to silence in healthcare. The impact of withholding information on healthcare professional burnout, patient safety and quality of care is significant. The paper concludes with a suggested future research agenda and additional recommendations.